Filling the GERD: evaluating hydroclimatic variability and impoundment strategies for Blue Nile riparian countries. Issue 4 (6th June 2016) - Zhang, Ying; Erkyihum, Solomon Tassew; Block, Paul
ABSTRACT: A modelling study is performed to evaluate interannual and decadal-scale streamflow variability into the Grand Ethiopian Renaissance Dam (GERD) reservoir and comparison of various filling strategies for hydropower and downstream releases to Sudan and Egypt from this dam. To capture these aspects, simulations of probabilistic streamflow via wavelet analysis are produced to define the propensity towards wetter or drier conditions for absolute, threshold and percentage-based filling strategies. Absolute filling strategies have lower uncertainty than percentage-based strategies, benefiting upstream planning; however, downstream releases may be near zero on occasion. Consensus among the riparian countries prior to initiation of filling is strongly encouraged.